Synthesis and biological activities of some novel substituted 2,N3,4,N5-tetrasubstituted 1,2,4-thiadiazolidine-3,5-diimines - Gupta R.; Srivastava K.; Pandeya S.N. (My University, 2025)
A series of 2,N3,4,N5-tetrasubstituted 1,2,4-thiadiazolidine-3,5-diimines (compds. 1a-i, 2) were synthesized and screened for their anticonvulsant and analgesic activity. The bis(4-methylphenyl) thiazolidine (1c) and bis(cyclohexyl) thiazolidine (2) were found more active than the reference drug phenytoin in MES tests. In analgesic test, the bis(3-methylphenyl) thiazolidine (1b), bis(4-methylphenyl) thiazolidine (1c) and bis(2-methoxyphenyl) thiazolidine (1f) were found statistically more significant in activity as compared to the reference drug, acetylsalicylic acid.